KEANEKARAGAMAN KERANG BIVALVIA DI SEPANJANG PASIR PANTAI WISATA KERANG MAS, DESA MUARA GADING MAS, KECAMATAN LABUHAN MARINGGAI, LAMPUNG - Aprilia Indah M Riani; Suparmono Suparmono; Darma Yuliana; Henny Wijayanti (Jurusan Akuakultur, Universitas Bangka Belitung, 2021)
East Lampung Regency has a coastal area of East Lampung with 316 ha. One of the coastal tourist areas owned by East Lampung Regency is Shells Mas Beach. This beach has a fairly long coastline where there are a lot of bivalves, but the inventory of the types of bivalves on the beach.The purpose of the research is to analyze both the species diversities of bivalves and physical also chemical conditions of the waters. The research methodology used purposive sampling method analysis of species abundance data, diversity index, and index dominance. From the result of the bivalve diversities on the coast, bivalve the most common found are is Matra grandis,it is found out that there is no dominating bivalve amongst them due to below normal dominating rate that is 0,08-0,16 to be considered low level (00,00<C≤0,30); middle with diversity index 2,18–2,70 (2<H’≤3); high with index diversity 0,85–0,94 (E>0,6). The highest abundance value at station 1 is 4787.01 ind/m3 and the lowest species abundance value at station 3 is138.75 ind/m3. From the results of the chemical physics measurements, it shows that it still is in the range of sea water quality standards. The Bivalve diversity relationship shows a positive correlation to the parameters of salinity, grain size, and sediment TSS. Meanwhile, it shows negative correlation for parameters DO, pH and temperature.